2023
DOI: 10.7759/cureus.33235
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of New Treatment Options for Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a type of nephropathy that is caused by a diabetic condition. Diabetic nephropathy is seen in type 1 and type 2 diabetes. End-stage renal disorders are brought on by DN. Diabetic nephropathy is thought to be linked to metabolic changes in the body. Proteinuria and glomerular filtration rate are the two most crucial diagnostic and prognosis measures for diabetic kidney disease (DKD), yet both have significant disadvantages. Novel biomarkers are thus increasingly required to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The study affirms the well-established association between hypertension and diabetic nephropathy, with 85% of subjects presenting with concurrent hypertension. Additionally, the coexistence of smoking (22%), obesity (63%), family history (49%), and elevated lipid levels (37%), emphasizes the intricate interplay of systemic factors contributing to the complex etiology of diabetic nephropathy [2]. Stratification of subjects based on blood glucose levels provides insights into the importance of glycaemic control.…”
Section: Resultsmentioning
confidence: 99%
“…The study affirms the well-established association between hypertension and diabetic nephropathy, with 85% of subjects presenting with concurrent hypertension. Additionally, the coexistence of smoking (22%), obesity (63%), family history (49%), and elevated lipid levels (37%), emphasizes the intricate interplay of systemic factors contributing to the complex etiology of diabetic nephropathy [2]. Stratification of subjects based on blood glucose levels provides insights into the importance of glycaemic control.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, patients with early DKD exhibit mild clinical symptoms and only present with microalbuminuria, which often goes unnoticed by patients [ 2 ]. In recent years, there have been advancements in treatment options for DKD patients, such as sodium-glucose transporter 2 (SGLT2) inhibitors [ 3 , 4 ]. Despite these advancements, some studies have shown that SGLT2 inhibitors are associated with an increased risk of genital infections [ 5 ] and are less effective in patients with severe renal impairment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAAS and SGLT2 inhibitors , although are not cures for DKD, if used early, can significantly reduce the risk of the development and progression of DKD. However, once DKD has advanced, their efficacy becomes limited (4).…”
Section: Introductionmentioning
confidence: 99%